2022
DOI: 10.1021/acs.analchem.2c02587
|View full text |Cite
|
Sign up to set email alerts
|

A Portable Sweat Sensor Based on Carbon Quantum Dots for Multiplex Detection of Cardiovascular Health Biomarkers

Abstract: The future of personalized diagnostics and treatment of cardiovascular diseases lies in the use of portable sensors. Portable sensors can acquire biomarker information in biological fluids such as sweat, an approach that mitigates the shortcomings of conventional hospital-centered healthcare. Low sensitivity, selectivity, and specificity remain bottlenecks for the widespread use of portable sensors. Herein, we demonstrate a portable sensor that simultaneously detects Na+, ascorbic acid, and human neuropeptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…One good example is a portable sensor for Na + , ascorbic acid, and human neuropeptide Y measurement from sweat. 116 These parameters were found to be correlated to cardiovascular health and could be further studied to establish more reliable disease indication. Saliva sampling could be another alternative physiological fluid in future diagnostic biosensor research whose feasibility has been validated by several studies.…”
Section: ■ Conclusion and Future Perspectivesmentioning
confidence: 99%
“…One good example is a portable sensor for Na + , ascorbic acid, and human neuropeptide Y measurement from sweat. 116 These parameters were found to be correlated to cardiovascular health and could be further studied to establish more reliable disease indication. Saliva sampling could be another alternative physiological fluid in future diagnostic biosensor research whose feasibility has been validated by several studies.…”
Section: ■ Conclusion and Future Perspectivesmentioning
confidence: 99%
“…There are a good number of literature reports where AA can be detected by enzymatic sensors. Recently, Zhang et al have reported a portable sweat sensor comprised of six electrodes based on carbon quantum dots for selective and sensitive recognition of AA [ 77 ], where the recognition phenomenon proceeds through an enzymatic catalytic reaction. CQD has been chosen as the electrode substrate material of the electrochemical sensors for immobilization of enzymes because of their large surface area [ 78 ] and abundant active sites for effectual reduction of the interfacial impedance to increase the sensitivity of the sensor [ 79 ].…”
Section: Nanomaterials-based Electrochemical Sensing Of Sweat Metabol...mentioning
confidence: 99%
“… ( a ) Schematic illustration of the mechanistic pathway of sensing, ( b ) amperometric response of the sensor in presence of 1–400 µM AA in artificial sweat, adopted with permission from Ref. [ 77 ]. …”
Section: Figurementioning
confidence: 99%
“…Wearable sensors can overcome this issue by conducting in situ sweat analysis for real-time results. [21][22][23][24][25][26] Wearable sensors have been demonstrated for detecting numerous metabolites such as glucose, [17,22,24,[27][28][29] uric acid, [30,31] ascorbic acid, [32,33] ions, [34][35][36][37][38] etc. A robust selfpowered sweat sensor was developed by Li and coworkers which shows the capability of sensing the concentration fluctuations of Na + and K + during exercises.…”
Section: Introductionmentioning
confidence: 99%